The Influence of Tiktok Live Streaming, Content Marketing on the Decision to Purchase Nike Shoes in FEB UGJ Students - Rivaldi, Rifky; Wibowo, Sandi Nasrudin; Misbak, Misbak (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2024)
With the very rapid development of technology using smartphones at this time, one of which is online shopping, consumers tend to shop via live streaming, one of which is available on the TikTok application with a variety of content. Therefore, this research aims to determine the influence of TikTok live streaming and content marketing on the decision to purchase Nike shoes among FEB UGJ students. The analytical method used in this research is multiple linear regression analysis and quantitative methods, using the SPSS application program data processing. Primary data was collected by distributing questionnaires to 105 FEB UGJ students. The research results show (1) There is a positive and partially significant influence between TikTok Live streaming on the decision to purchase Nike shoes for FEB UGJ students. (2) There is a partial positive and significant influence between Content marketing on the decision to purchase Nike shoes for FEB UGJ Students. (3) There is a significant positive influence simultaneously between TikTok live streaming and content marketing on the decision to purchase Nike shoes for FEB UGJ students.